The value of the low-dose dexamethasone suppression test in the differential diagnosis of hyperandrogenism in women. - Kaltsas, G; Isidori, A; Kola, B; Skelly, R; Chew, S; Jenkins, P; Monson, J; Grossman, AB; Besser, G (2003)
We studied 211 hyperandrogenic women with respect to clinical presentation, basal androgen levels, and the degree of cortisol and androgen suppression during a 48-h low-dose (2 mg) dexamethasone-suppression test (LDDST) to exclude ovarian and adrenal tumors. In 42 women with elevated testosterone levels, 21 of whom failed to suppress testosterone during the LDDST, the response of serum androgen levels during a 4-wk administration of 7.5 mg prednisolone in a reverse circadian regimen was also assessed. These results were compared with an additional 17 patients with histologically proven androgen-secreting tumors. Clinical presentation alone was suggestive of a virilizing tumor in 70% of patients with tumors. Serum testosterone, although occasionally only marginally elevated, was the sole androgen that was elevated in every patient with a tumor. After the LDDST, none of the patients with tumors obtained either a greater than 40% reduction or normalization of the previously elevated testosterone levels, whereas 88% of patients with nontumorous hyperandrogenism showed either normalization or suppression of more than 40%. With one exception, all of the patients with nontumorous hyperandrogenism who showed inadequate suppression of testosterone during the LDDST, and were treated with prednisolone, normalized the previously elevated androgens after 1 month of administration. In summary, in women presenting with hyperandrogenism, lack of testosterone suppression during the LDDST is associated with 100% sensitivity and 88% specificity in distinguishing patients with ovarian and adrenal androgen-secreting tumors from patients with nontumorous hyperandrogenism in this small series. The LDDST is an easy to perform screening test that can also identify causes of hyperandrogenism due to altered glucocorticoid secretion.